2011
DOI: 10.1074/jbc.m111.256206
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor-4 (TLR4) Down-regulates MicroRNA-107, Increasing Macrophage Adhesion via Cyclin-dependent Kinase 6

Abstract: Toll-like receptors (TLRs) modulate the expression of multiple microRNAs (miRNAs). Here, we report the down-regulation of miR-107 by TLR4 in multiple cell types. The miR-107 sequence occurs in an intron within the sequence encoding the gene for pantothenate kinase 1␣ (PanK1␣), which is regulated by the transcription factor peroxisome proliferator-activating receptor ␣ (PPAR-␣). PanK1␣ is also decreased in response to lipopolysaccharide (LPS). The effect on both miR-107 and PanK1␣ is consistent with a decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 41 publications
(39 reference statements)
2
40
1
2
Order By: Relevance
“…Interestingly, it has been reported that miR-129 overexpression leads to G1 cell cycle arrest and eventually to cell death (71). Since miR-107 has also been found to arrest the cell cycle in the G1 phase (19,25,37,57), we could speculate that this mechanism underlies our observations in GH3 and SH-SY5Y cells. However, further studies are necessary to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 44%
“…Interestingly, it has been reported that miR-129 overexpression leads to G1 cell cycle arrest and eventually to cell death (71). Since miR-107 has also been found to arrest the cell cycle in the G1 phase (19,25,37,57), we could speculate that this mechanism underlies our observations in GH3 and SH-SY5Y cells. However, further studies are necessary to confirm this hypothesis.…”
Section: Discussionsupporting
confidence: 44%
“…For example, miR-181a was found to be concurrently upregulated with IL-1α, IL-1β, IL-6, and TNF-α in a mouse acute inflammatory state via a TLR4-dependent pathway (21). MiR-107, which was downregulated in response to LPS in multiple cell types (22), and let-7i, which was decreased in LPSstimulated cholangiocytes (23), were found to be affected in a MyD88-and NF-κB-dependent manner. Similar coexpression patterns between these miRNAs and TLR signaling compartments in our study might support those results.…”
Section: Lps-induced Mirnas In Tlr Signalsmentioning
confidence: 99%
“…miR-107 and miR-186 directly regulate CDK6 expression by interacting with the 3′-UTR of its mRNA to inhibit cancer cell proliferation [32,33]. Elizabeth et al demonstrated that Toll-like Receptor-4 (TLR4) down-regulated miR-107, thus increasing CDK6 expression and promoting macrophage adhesion [32]. However, it has been shown that individual or combined deletion of CDK4 and CDK6 does not affect the proliferation of normal cells [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…CDKs perform various functions by regulating the cell cycle and gene expression, indicating their involvement in diverse biological processes [31]. miR-107 and miR-186 directly regulate CDK6 expression by interacting with the 3′-UTR of its mRNA to inhibit cancer cell proliferation [32,33]. Elizabeth et al demonstrated that Toll-like Receptor-4 (TLR4) down-regulated miR-107, thus increasing CDK6 expression and promoting macrophage adhesion [32].…”
Section: Discussionmentioning
confidence: 99%